Penerapan Model Kooperatif Tipe Teams Games Tournament (TGT) terhadap Pemecahan Masalah Berbantuan Aplikasi Kahoot pada Pembelajaran Pendidikan Pancasila Kelas X B di SMA Negeri 2 Singaraja - Ni Kadek Reka Puspita; I Wayan Kertih; Ni Nyoman Asri Sidaryanti; Sukadi; I Wayan Budiarta (CV. Alim's Publishing, 2026)
This study focuses on examining the effect of using the cooperative learning model type Teams Games Tournament (TGT) assisted by Kahoot in optimizing students’ problem-solving skills. The research method applied was Classroom Action Research (CAR), conducted through several cycles with stages including planning, action implementation, observation, and reflection. The subjects of this study were students of class X.B at SMA Negeri 2 Singaraja. The results of the study indicate a significant improvement in students’ problem-solving abilities after the implementation of the TGT model assisted by Kahoot. In cycle II, the students’ average score reached 88.15, with a learning mastery level of 84.21%. Therefore, it can be concluded that the majority of students had met the minimum learning mastery indicators. In addition, the learning process became more active, interactive, and enjoyable, which increased student engagement in the classroom. In conclusion, the cooperative learning model Teams Games Tournament (TGT) assisted by the Kahoot application has a positive impact on improving students’ problem-solving abilities. Therefore, the use of game-based digital learning models and media is recommended to enhance the quality of both the learning process and learning outcomes.